A Study On Share Value Relational Capital And Smes Business Performance: A Resource Based Theory Perspective - Sukrisno Sukrisno; Pranoto Pranoto; Hartoyo Suhari; Haniek Listyorini (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research aims to build a new conceptual model based on shared value relational capital and synergized Network assets to improve innovation capabilities in the context of Small and medium enterprises (SME) business performance. A structural methodology study was adopted in this research and involved 180 small and medium business owners or managers involved in this research in the data collection process. Data analysis for this research uses AMOS 25 software. The findings show that there are two strategic paths for improving SME business performance. Strengthening the share value of relational capital and synergy network assets is a key strategy for improving SME business performance. The sample frame taken from SMEs in Central Java province is a limitation in this research in building the generalization strength of the concept of share value of relational capital. So a form of replication of similar research is needed to achieve a fairly broad generalization of the new concept. The theoretical implications in this research are related to the application of resource-based theory in the study of marketing and strategy management. Some are managerial impressive for SME business actors who want to improve their business performance. This study has the originality of a pioneering study regarding the explanation of the role of share value relational capital and synergy network assets, which are expected to be able to provide a role in bridging innovation capabilities and improving SME business performance.